Urban livability, a category to analyze social housing in Mexico in the 21st century (REVISTA NODO, 2022)
The reflection on living in the house begin to be carried out from the social point of view, to understand that it transcends the territory where it is located. As Borja points out, “housing is one of the elements that make up the city; but, without being integrated into the city, housing is not adequate” (2016: 8). Therefore, housing is the element of first instance that allows the person to function in the city but it is necessary to find it inserted into the urban livability conditions that the city offers.Tthis article aims to recognize the integration of livability in social housing understood as a form of urbanization that arises from housing policies. The method starts from the theoretical reflection of the concepts of urban livability, social housing and periphery, to understand them as integral processes within the city. The results identify minimal elements inside and outside that social housing located in the periphery must contain in relation to urban livability to satisfy the basic needs of its population within the Mexican context in the 21st century.
Keywords: urban livability; periphery; segregation; social housing